Formation of titanium-containing phosphates in polyphosphate acids' melts - Затовський, І. (Київський національний університет імені Тараса Шевченка, 2010)
Phase relationships in the polyphosphate acids- containing melted systems of Ti–P2O5–Н2O, Ti2O3–P2O5–Н2O, TiN–P2O5–Н2O andwith presents of alkali oxides (lithium, sodium and potassium) were investigated. Conditions of Ti(PO3)3 and TiP2O7 crystallization wereidentified. High stability of Ti (III) in melts of polyphosphate acids for temperature range of 350–600 °С was shown. Suitable pathway ofTi(PO3)3 preparation was proposed. UV/VIS, FTIR and EPR spectra of titanium (III) metaphosphate were discussed. The scheme of thermal decomposition of latter compound was determined on the basis of DTA data

Досліджено закономірності утворення фосфатів титану в розплавах поліфосфорних кислот для систем типуTi–P2O5–Н2O, Ti2O3–P2O5–Н2O, TiN–P2O5–Н2O та в присутності оксидів лужних металі (літій, натрій, калій). Встановлено особливості кристалізації фосфатів складів Ti(PO3)3 і TiP2O7. Виявлено високу стабільність титану (ІІІ) в розплавах поліфосфорних кислот за температур 350–600 °С. Розроблено препаративні методики синтезу Ti(PO3)3. Для метафосфату титану (ІІІ) охарактеризовані електронні, інфрачервоні та ЕПР-спектри. За даними диференціально-термічного аналізу з'ясованосхему термічного розкладу Ti(PO3)3 на повітрі.
Конденсовані фосфати титану у розплавах поліфосфорних кислот
Keywords: -; -; -